An alternative novel tool for DNA editing without target sequence limitation: the structure-guided nuclease. Issue 1 (December 2016) - Xu, Shu; Cao, Shasha; Zou, Bingjie; Yue, Yunyun; Gu, Chun; Chen, Xin; Wang, Pei; Dong, Xiaohua; Xiang, Zheng; Li, Kai; Zhu, Minsheng; Zhao, Qingshun; et al.
Abstract Engineered endonucleases are a powerful tool for editing DNA. However, sequence preferences may limit their application. We engineer a structure-guided endonuclease (SGN) composed of flap endonuclease-1 (FEN-1), which recognizes the 3′ flap structure, and the cleavage domain of Fok I (Fn1), which cleaves DNA strands. The SGN recognizes the target DNA on the basis of the 3′ flap structure formed between the target and the guide DNA (gDNA) and cut the target through its Fn1 dimerization. Our results show that the SGN, guided by a pair of gDNAs, cleaves transgenic reporter gene and endogenous genes in zebrafish embryonic genome.